2016
DOI: 10.1007/s13594-016-0292-3
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of PrtS in Streptococcus thermophilus is not enough in certain strains to achieve rapid milk acidification

Abstract: The acquisition of prtS by Streptococcus thermophilus strains allowed hydrolysis of caseins into peptides and then to increase their growth in milk. This leads to faster milk acidification, which is important in dairy industry. However, some strains harboring the same allele of prtS present different acidification rates, which could be explained by a difference in the regulation of prtS expression. We chose two strains with the same allele of prtS (including the same promoter region): one, PB302, is with high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…lactis cells, and the inhibitory potency is modulated in an intracellular environment rich in amino acids such as isoleucine, leucine, and valine [ 89 , 90 ]. While regulating the proteolytic system, the CodY repressor acts as a blocking agent that binds to the CodY operator sequence (AATTTTCWGAAAATT) and prevents RNA polymerase from accessing the promoter sites of individual components of the proteolytic system [ 4 , 91 , 92 , 93 ]. To sum up, when the intracellular concentration of the amino acids isoleucine, leucine, and valine increases, several of these amino acids attach to the allosteric site of the CodY repressor by changing the conformation of this protein in a such way that it allows it to bind to the operator in the DNA; consequently, this combination blocks the transcription of genes responsible for enzyme synthesis.…”
Section: Regulation Of the Proteolytic Systemmentioning
confidence: 99%
“…lactis cells, and the inhibitory potency is modulated in an intracellular environment rich in amino acids such as isoleucine, leucine, and valine [ 89 , 90 ]. While regulating the proteolytic system, the CodY repressor acts as a blocking agent that binds to the CodY operator sequence (AATTTTCWGAAAATT) and prevents RNA polymerase from accessing the promoter sites of individual components of the proteolytic system [ 4 , 91 , 92 , 93 ]. To sum up, when the intracellular concentration of the amino acids isoleucine, leucine, and valine increases, several of these amino acids attach to the allosteric site of the CodY repressor by changing the conformation of this protein in a such way that it allows it to bind to the operator in the DNA; consequently, this combination blocks the transcription of genes responsible for enzyme synthesis.…”
Section: Regulation Of the Proteolytic Systemmentioning
confidence: 99%
“…However, the sole presence of prtS is not sufficient for the rapid milk acidification by S. thermophilus. Milk acidification seems to be a complex phenotypic trait, which involves the overexpression of several genes (Galia et al, 2016). Furthermore, it was demonstrated that S. thermophilus strains, irrespective of the prtS +/− status, may present cellassociated extracellular peptidase activities.…”
Section: Proteolytic Systemmentioning
confidence: 99%
“…Despite the previous information, not all the S. thermophilus strains possess PrtS, e.g., strain CNRZ1066 lacks prtS gene and, in contrast, strain LMD-9 displays strong proteolytic activity due to the presence and expression of prtS gene [36]. It has been shown that for high proteolytic activity, the presence of a putative CodY-box is necessary in their promoter region, which is a feature of the transcriptional pattern of CodY-regulated genes that are able to bind promoters of 14 genes belonging to the proteolytic system, including PrtS [37]. It has been shown that the interaction between S. thermophilus, with or without PrtS, and Lactobacillus, especially Lb.…”
Section: Specificity Of Streptococcus Thermophilus Proteinase Prtsmentioning
confidence: 99%